IMPROVING QUALITY OF SERVICE AT PUBLIC TRANSPORT BY USING FOCUS GROUP METHOD - Azamatovich, Berdiyorov Temur (International Journal of Psychosocial Rehabilitation, 2020)
The article deals with the results of marketing research by the method of focus groups on the observation of the quality of public land transport services. On the basis of analysis of research results preliminary groups of properties and characteristics of transport service are formed, "points of contact" of consumers of service with the supplier of service are specified, and the relation of consumers of service to made changes in system of transport service are exposed.